Privación de libertad en los establecimientos de Medellín (2012)
The research "the state of the fundamental rights of people deprived of liberty in correctional and prison institutions in Medellín" dealt with defining the historical and the current context of institutions of deprivation of liberty in the municipality of Medellín. Based on that, those that have existed in the municipality are described, as well as those which currently exist for the deprivation of liberty for the members of the National Police, the National Army, and civilian adult men and women. As a way to demonstrate that the deprivation of liberty is discriminated in various types of those institutions, and that those which were built as the solution to huge prison and penitentiary problems, are simply part of the problem.